Ciao: A Collaborative, Immersive Architectural Layout System - Sung, Un-Jae; Yang, Jae-Heon; Wohn, K. (International Journal of Virtual Reality, 2000)
This paper presents the design of a multiuser, large-scale 3-D layout system: Collaborative Immersive Architectural layout (CIAO). In contrast to many existing systems that sacrifice responsiveness to maintain consistency, CIAO achieves optimal response and notification time without compromising awareness or consistency. The optimal responsiveness is achieved by a new multicastbased, optimized concurrency control mechanism. Even operations on a group of related objects do not entail any latency for concurrent control. We also present the multiuser interfaces of CIAO that provide some sense of isolation as well as rich awareness.